Ten golden rules for restoration to secure resilient and just seagrass social‐ecological systems - Richard K. F. Unsworth; Benjamin L. H. Jones; Chiara M. Bertelli; Lucy Coals; Leanne C. Cullen‐Unsworth; Anouska F. Mendzil; Samuel C. Rees; Flo Taylor; Bettina Walter; Ally J. Evans (Plants, People, Planet)
Societal Impact Statement Seagrass meadows are a globally important habitat subject to significant loss. As efforts to restore these sensitive habitats are hampered by their high cost and low levels of reliability, rigorous guidance is required to improve effectiveness and ensure they are cost‐effective. Here, we define 10 golden rules for how we can undertake seagrass restoration. We do this by considering that for seagrass restoration to be successful, it needs to take place with people and not against people. The framework we present aims to direct efforts for seagrass restoration that are holistic and achieve broad goals for people, biodiversity and the planet. Summary The world has lost a significant proportion of its seagrass, and although glimmers of hope for its recovery exist, losses and degradations continue. First and foremost, evidence highlights the need to put the world on a global pathway to seagrass net gain. Achieving this outcome requires that conservation of what remains is a priority, but reaching net gain requires seagrass coverage to increase at rates unlikely to be achieved naturally; large‐scale active restoration is required to fill this gap. Novel finance mechanisms aligned to the climate emergency and biodiversity crises are increasingly leading to larger scale restoration projects. However, no clear framework exists for developing or prioritising approaches. With seagrass restoration expensive and unreliable, rigorous guidance is required to improve effectiveness and ensure it is cost‐effective. Building on evidence from terrestrial and marine sources, here, we apply the ‘10 golden rules’ concept, first outlined for reforestation and later applied to coral reefs, to seagrass restoration. In doing so, we follow international standards for ecological restoration and view seagrass restoration in a broad context, whereby regeneration can be achieved either by planting or by enhancing and facilitating natural recovery. These rules somewhat differ from those on reforestation and coral reef restoration, principally due to the relative immaturity of seagrass restoration science. These 10 golden rules for seagrass restoration are placed within a coupled social‐ecological systems context, and we present a framework for conservation more broadly, to achieve multiple goals pertaining to people, biodiversity and the planet.